Telemedicine and molecular Sars-CoV-2 early detection to face the COVID-19 pandemic - Cherem, José; Pylro, Victor Satler; Poles, Katia; Carvalho, Richardson Costa; Carvalho, Ewerton; Santos, Juliana Anacleto dos; Barçante, Joziana Muniz de Paiva (Universitas Diponegoro, 2022)
The COVID-19 pandemic brought a series of challenges to the academic community. Social distancing measures imposed the interruption of face-to-face activities besides the implementation of remote work and online classes. For safe and gradual return, the monitoring of individuals, quick detection of infection, contact tracing, and isolation of those infected became essential. In this sense, we developed strategies to face the pandemic at the Federal University of Lavras (UFLA) - Brazil. A Telemedicine Program (TeleCovid) and the assemblage of a laboratory for SARS-CoV-2 molecular diagnosis (LabCovid) were essential measures for monitoring, preventing, and controlling outbreaks at the university. TeleCovid works with a team of students who guide and answer questions regarding COVID-19 and, when necessary, make the referral for online consultation with medical professionals. In the suspicion of SARS-CoV-2 infection, the doctor refers the patient for testing at LabCovid. LabCovid performs the sample collection using nasal swabs, followed by processing samples by the RT-qPCR method. We have placed all positive patients in isolation and tested their contacts. This approach meant that positive cases were identified early, thus avoiding outbreaks in different environments in face-to-face activities.Keyword: Covid-19; university, RT-qPCR